2014
DOI: 10.1080/09168451.2014.936353
|View full text |Cite
|
Sign up to set email alerts
|

Lgr4 is required for endometrial receptivity acquired through ovarian hormone signaling

Abstract: Previously, using the Keratin5-Cre transgenic mouse model we reported that female Lgr4-conditional KO mice (Lgr4K5 KO) showed subfertility with defective stromal decidualization due to abnormal development of the uterine gland. However, the impact of the LGR4 defect on luminal epithelial cells was not investigated in the previous report. Here, we focused on the receptive state of the luminal epithelium in Lgr4K5 KO mice that received ovarian hormone treatment. In Lgr4K5 KO mice, progesterone failed to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Lgr4 has been implicated in a broad array of biologic processes. Whole-body Lgr4 deletion is frequently embryonic lethal (55), with survivors bearing a host of developmental defects affecting bone (17,18,(56)(57)(58), blood (22,26), brain (13,59), eye (14,15,60), intestines (61,62), kidneys (63-65), bile duct (19), and reproductive organs (29,(66)(67)(68)(69)(70)(71). Several of these phenotypes were reported in humans bearing a nonsense mutation LGR4 allele (37).…”
Section: Discussionmentioning
confidence: 99%
“…Lgr4 has been implicated in a broad array of biologic processes. Whole-body Lgr4 deletion is frequently embryonic lethal (55), with survivors bearing a host of developmental defects affecting bone (17,18,(56)(57)(58), blood (22,26), brain (13,59), eye (14,15,60), intestines (61,62), kidneys (63-65), bile duct (19), and reproductive organs (29,(66)(67)(68)(69)(70)(71). Several of these phenotypes were reported in humans bearing a nonsense mutation LGR4 allele (37).…”
Section: Discussionmentioning
confidence: 99%
“…To date, despite the fact that several GPCRs are expressed in the uterus during the peri-implantation period, only a few have been identified as critical regulators of uterine receptivity and embryo implantation. These are leucine-rich repeat-containing GPCR 4 (LGR4) (9)(10)(11), lysophosphatidic acid receptor 3 (LPAR3) (12), and the kisspeptin receptor (KISS1R) (13)(14)(15)). LGR4 appears to couple to Ga s, LPAR3 couples to Ga q/11 and Ga i/0 (16), and KISS1R couples to Ga q/11 (16,17).…”
mentioning
confidence: 99%
“…LGR4 appears to couple to Ga s, LPAR3 couples to Ga q/11 and Ga i/0 (16), and KISS1R couples to Ga q/11 (16,17). Deletion of epithelial LGR4 in the mouse results in reduced endometrial gland formation (adenogenesis), persistent epithelial E2 receptor a signaling, P4 resistance, and a lack of decidualization (9)(10)(11). Deletion of LPAR3 results in persistent epithelial PR signaling and the inability to exit the prereceptive phase of early pregnancy (12).…”
mentioning
confidence: 99%
“…In vivo studies have demonstrated that this receptor plays an essential role during development as Lgr4-deficient embryos display embryonic and perinatal lethality [12]. Moreover, developmental defects have been reported for homozygous mice in many organs, including among others, altered tubulogenesis, impaired branching morphogenesis, renal hypoplasia, corneal dysgenesis or gallbladder agenesis [13][14][15][16][17][18][19][20][21][22][23][24][25]. In line with expression of Lgr4 in progenitors/stem cells, its deficiency generally correlates with reduced cell proliferation in tissues [7,15,19,23,[26][27][28][29].…”
Section: Tissue Expression and In Vivo Functionmentioning
confidence: 94%
“…In line with expression of Lgr4 in progenitors/stem cells, its deficiency generally correlates with reduced cell proliferation in tissues [7,15,19,23,[26][27][28][29]. Moreover, though premature differentiation has been reported in Lgr4-deficient embryos [17,21,30], Lgr4 deficiency has been mainly described to be associated with impaired or retarded cell differentiation [23,24,28,29,[31][32][33]. Such phenotypes have been demonstrated to be associated with decreased Wnt signaling in intestinal, liver and dental epithelia as well as in peritubular myoid cells in testis [7,23,28,31,34,35].…”
Section: Tissue Expression and In Vivo Functionmentioning
confidence: 99%